KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS DEPOK I KABUPATEN SLEMAN - Lestari, Oktavia Ningrum Puji; Putranto, Arif Kuncoro Dwi (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
Providing public services to the community is one of the most important main tasks for the government. One form of service provided is in the health sector. One of the government's efforts to provide health services to the community is that in every sub-district a government agency has been built as a community health service delivery unit, namely a community health center (Health Center). This research aims to determine the quality of health services at the Depok I Health Center, Sleman Regency. This type of research is descriptive qualitative, the data sources used are primary data and secondary data. The data collection techniques used were observation, interviews and documentation. The indicators in this research are (1) simplicity, (2) clarity, (3) certainty of time, (4) accuracy, (5) security, (6) responsibility, (7) completeness of facilities and infrastructure, (8) ease of access, (9) discipline, politeness and friendliness, (10) comfort.Keyword: Quality Health Services; Health Center.